Scientific Research; Instructions from the Holy Quran - Uddin, Muhammad Athar; Ferdous, Fouzia (IIUC Studies, 2015)
Science is the branch of knowledge that deals with the material world. In scientific research it is necessary to know "How does our knowledge of physical world expand?" and "What are the principles of scientific research?" In fact scientific research is a combination of experimental works and intellectual activity. The Almighty Allah has given specific fundamental properties to every materials of the universe. The Scientist can only discover very few of those properties and apply them in integrated form when and where necessary. Continuation of scientific research and advancement of the technology is possible only because of the unchangeable fundamental properties of all materials of the universe formulated by the Almighty Allah. As per Quranic instructions no scientific research is accepted without proven reason and the scientific theories contradictory to the Holy Quran must be rejected. IIUC Studies Vol.9 December 2012: 225-232